Data on rainforest birds from line transect surveys in the Kalakad - Mundathurai Tiger Reserve, Tamil Nadu, India - Raman, T. R. Shankar (Dryad, 2022)
This dataset contains data on rainforest bird communities collected along
line transects in Kalakad - Mundanthurai Tiger Reserve, Tamil Nadu, India,
as part of doctoral research leading up to the following thesis:Raman, T.
R. S. 2001. Community ecology and conservation of mid-elevation tropical
rainforest bird communities in the southern Western Ghats, India. PhD
thesis, Indian Institute of Science, Bangalore.Part of the data (from
transects T2 and T3, in particular) was used in the following
publication:Raman, T. R. S. 2003. Assessment of census techniques for
inter-specific comparisons of tropical rainforest bird densities. Ibis
145: 9-21. http://doi.org/10.1046/j.1474-919X.2003.00105.xThe Raman (2003)
publication also uses bird point count data (from T2 and T3) available in
a related dataset:  Raman, T. R. S.,  Mudappa, D.,
Jeganathan, P., Joshi, N. V., Sukumar, R. 2022. Data on bird communities
and vegetation in relation to altitude and habitat alteration in the
Kalakad - Mundanthurai Tiger Reserve, Tamil Nadu, India. Dryad, Dataset,
https://doi.org/10.5061/dryad.41ns1rngj GEOGRAPHICAL AREA:
Kalakad-Mundathurai Tiger Reserve (KMTR), 895 km² sanctuary located
between 8°25′ to 8°53′ N and 77°10′ to 77°35′ E in Tamil Nadu state in the
Western Ghats mountain range of India. TAXONOMIC SCOPE: Birds, mammals
ACKNOWLEDGEMENT: I am grateful to P. Pavithra for help with data entry and
compilation.
Bird data are from 600 m long line transect surveys surveyed typically in
about 60 min duration in the early morning hours. The methods for bird
sampling are as described in Raman (2003) and in this doctoral thesis:
Raman, T. R. S. 2001. Community ecology and conservation of mid-elevation
tropical rainforest bird communities in the southern Western Ghats, India.
PhD thesis, Indian Institute of Science, Bangalore. All transects were
censused during the first 3 h after sunrise when bird activity was highest
in the area (unpublished data). The 600-m-long transect was walked in
about 1 h, at a slow, uniform pace. All birds seen (perched or flying
under the canopy) or heard were recorded as to species, number (wherever
possible) and perpendicular distance in the following metre classes: 0–5,
5–10, 10–15, 15–20, 20–30, 30–50 and 50–100. The further distance classes
were wider to minimize errors in distance estimation (verified using a
range finder whenever possible).
Besides the README.TXT file, this dataset contains the following 3
comma-delimited text files with data in columns as explained
below.01_transectlocations.csvThis file contains details of transect in
mature rainforests and plantations and plantation-forest edgesTransect:
Unique ID number or name of a 600 m long line transectLatitudeN:
Approximate latitude in decimal degrees North of the midpoint of the
transectLongitudeE: Approximate longitude in decimal degrees East of the
midpoint of the transectLocationDetails: Description of
location02_transectbirds.csvThis file contains the data on birds from 5
minute variable radius point count surveysTransect: Unique ID number or
name of a 600 m long line transectDate: Date of survey of the specified
line transectStartTime: Start time of the transect (transects were
supposed to be of 60 min duration in morning hours)EndTime: End time of
the transect (transects were supposed to be of 60 min duration in morning
hours)Startweather: Weather at the start of the transectEndweather:
Weather at the end of the transectTime: Specific time of
observationSpecies_old: Old common name of the bird speciesSpecies:
English common name (India) of the bird species as used in the Ebird India
portal in 2022 BirdMamm: Category indicating Bird or MammalFlock: Category
indicating whether the observation of that species was of a detection (1
or more birds detected as indicated in the next column) or a flock of
birds (a flock of more than 1 individual was present but could not be
counted and is just recorded as 1 in the next column)Number: Number of
individuals detectedPD: Perpendicular distance of the detected bird from
the transect line in the following distance classes in metres: 0-5; 5-10,
10-15, 15-20; 20-30; 30-40; 40-50; 50-100; Note that for mammals the
following distance classes in metres were also used: 0-10 and 10-20; NA =
not available HSF: Code indicating H = heard; S = seen; F = flying under
the canopy (UC) or less than 5 m over the canopy (OC)Location: 25 m
segment location within transect line. Most transects started at A1 and
had points marked every 25 m in 100 m chunks: A1...A4, B1...B4, ... upto
F1...F4, after which it ended with X at the 600 m point. Alphabet codes
varied on longer trails or where transects did not begin at A1.LR: Portion
within 25 m segment and side of transect where bird was observed. L =
left; R = right; BL = bottom left; BR = bottom right; ML = mid left; MR =
mid right; TL = top left; TR = top right  Remarks: notes and
remarks; (includes some codes: *: in mixed species flock; T: total count
of number of individuals;  diff/DIFF/DF: different detection from
conspecific; detected on the same point; GP: flock; CC: counter-calling
individuals) MHP: Whether the bird was in a mixed hunting party or mixed
species flock (Y = yes; N = no)03_birdnames.csvThis file contains bird
species codes and matching common and scientific namesSpecies_old: Old
common name used for the bird speciesSpecies: English common name (India)
of the bird species as used in the Ebird India portal in
2022.ScientificName: Scientific name of bird species (following the
Clements classification) as used in the Ebird India portal
(https://ebird.org/india)
Keywords: FOS: Natural sciences; bird communities; tropical rainforest; Western Ghats; Agasthyamalai Hills; Ashambu Hills